Water consumption in the production process of the sugar-energy industry: case study in the northwest of São Paulo (Brazil) - Barroquela, Weslei Brito [UNESP]; Bega, João Miguel Merces; Anicio, Sabrina de Oliveira; de Oliveira, Jefferson Nascimento [UNESP] (Zeppelini Editorial e Comunicacao, 2023)
Brazil is the world’s largest producer of sugarcane. The importance of rational, sustainable, and efficient management of resources in the production process of the Brazilian sugar-energy industry is remarkable, mainly related to water use. In this context, the present paper aimed to analyze, in the last decade, the consumption of water in the productive process of Vale do Paraná S/A Álcool e Açúcar plant, in addition to elucidating the technologies implemented in the industrial area that contributed to the reduction of consumption. The methodology adopted consisted of obtaining data and information from bibliographic researches, technical bulletins, and field visits. The sugar-energy plant showed a 34.88% reduction in water consumption in the last decade, obtaining 0.86 m3 ton-1 in 2012 and 0.56 m3 ton-1 in 2021 of processed sugarcane, which can be particularly important in intense periods of drought, such as those experienced in recent years. The main technologies that contributed to this reduction were: the dry cleaning of sugarcane; the use of closed circuits; condensate recovery; water reuse; and the implementation of a flow rate measurement system. The company reached a lower consumption than required for the year 2024, but there is no limit to reduction. In the case of the plant under study, it was observed that special attention should be given to industrial effluents, mainly vinasse, with the possible implementation of more treatment steps before application in the field as fertigation.
Consumo de água no processo produtivo da indústria sucroenergética: estudo de caso no noroeste paulista (Brasil)
Keywords: industrial technologies; sugarcane; water resources planning; water reuse